Geographic Information Systems and Decision Processes for Urban Planning: A Case Study of Rough Set Analysis on the Residential Areas of the City of Cagliari, Italy - Corrado Zoppi; Sabrina Lai (European Regional Science Association (ERSA), 2006)
In Italy, urban planning is based on the city Masterplan. This plan identifies the future urban organization and a system of zoning rules. Land-use policies are based on these rules. The zoning rules should synthesize environmental and spatial knowledge and policy decisions concerning the possible futures, with reference to the different urban functions. In this essay, a procedure of analysis of the city Masterplan of Cagliari, the regional capital city of Sardinia (Italy), is discussed and applied. This procedure is referred to the residential areas. The procedure tries to explain the urban organization of the housing areas using a system of variables based on the integration of different branches of knowledge concerning the urban environment. The decisions on the urban futures that the zoning rules entail are critically analyzed in terms of consistency with this knowledge system. The procedure consists of two phases. In the first phase, the urban environment is analyzed and described. This is done by defining and developing a geographic information system. This system utilizes a spatial analysis approach to figure out the integration of the residential areas into the urban fabric. The second phase is inferential. Based on the geographic information system developed in the first phase, a knowledge discovery in databases (KDD) technique, the rough set analysis (RSA), is applied. This technique allows to recognize the connection patterns between the urban knowledge system and the city planning decisions. The patterns, the decision rules, which come from the RSA implementation are important starting points for further investigation on the development of decision models concerning urban planning.
Keywords: 330